1998
DOI: 10.1161/01.res.82.3.346
|View full text |Cite
|
Sign up to set email alerts
|

ATP-Sensitive K + Channels, Adenosine, and Nitric Oxide–Mediated Mechanisms Account for Coronary Vasodilation During Exercise

Abstract: Abstract-We previously reported that combined blockade of adenosine receptors and ATP-sensitive Kϩ channels (K ϩ ATP channels) blunted but did not abolish the response of coronary blood flow to exercise. This study tested the hypothesis that the residual increase in coronary flow in response to exercise after adenosine receptor and K ϩ ATP channel blockade is dependent on endogenous NO. Dogs were studied at rest and during a four-stage treadmill exercise protocol under control conditions, during K ϩ ATP channe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
172
3
2

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 178 publications
(184 citation statements)
references
References 52 publications
(59 reference statements)
6
172
3
2
Order By: Relevance
“…Indeed, animal studies have indicated substantial redundancies in vasodilator mechanisms. In the coronary vasculature, for example, the important role of NO in coronary vasodilation during exercise was unmasked only after blockade of K ϩ ATP channels and adenosine receptors (57). Under exercise conditions, when NO production is inhibited, it is feasible that these other agents provide an increased contribution to exercise hyperemia and thus maintain normal exercise blood flow.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, animal studies have indicated substantial redundancies in vasodilator mechanisms. In the coronary vasculature, for example, the important role of NO in coronary vasodilation during exercise was unmasked only after blockade of K ϩ ATP channels and adenosine receptors (57). Under exercise conditions, when NO production is inhibited, it is feasible that these other agents provide an increased contribution to exercise hyperemia and thus maintain normal exercise blood flow.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 This increase in CBF appeared to result from an increase of MV O 2 with secondary coronary vasodilation, 14 inasmuch as coronary sinus PO 2 decreased significantly after L-NNA, indicating increased myocardial oxygen extraction. NO can compete with oxygen at cytochrome oxidase, 1 and nonselective NOS inhibition has been reported to increase both total body and skeletal muscle oxygen consumption in normal dogs.…”
Section: No In the Normal Heartmentioning
confidence: 94%
“…Nitric oxide stimulates relaxation through a cGMP cascade. In this scenario, blockage of any one vasodilatory pathway can be compensated by the others until O 2 supply matches consumption (Ishibashi et al 1998). A variation on this theme is that adenosine acts to relax the smooth muscle cell exclusively through stimulation of the ATP-sensitive K + channel and, furthermore, is responsible for NO release from the endothelium (Hein and Kuo 1999;Murrant and Sarelius 2000).…”
Section: Mammary Blood Flowmentioning
confidence: 99%